Prognostic role of distant disease-free interval from completion of adjuvant trastuzumab in HER2-positive early breast cancer: analysis from the ALTTO (BIG 2-06) trial - Lambertini, Matteo (ESMO Open, 2020)
BACKGROUND: In HER2-positive breast cancer, time elapsed between completion of (neo)adjuvant trastuzumab and diagnosis of metastatic disease (‘trastuzumab-free interval’, TFI) is crucial to choose the optimal first-line treatment. Nevertheless, there is no clear evidence to support its possible prognostic role. METHODS: In the Adjuvant Lapatinib and/or Trastuzumab Treatment Optimisation (ALTTO) trial, patients with HER2-positive early breast cancer were randomised to 1 year of either trastuzumab alone, lapatinib alone, their sequence or their combination. This exploratory analysis included only patients in the trastuzumab alone or trastuzumab plus lapatinib arms who developed a distant disease-free survival (DDFS) event. Overall survival (OS) was defined as time between date of DDFS event and death; age at diagnosis, tumour size and hormone receptor status were the variables included in the multivariate models. RESULTS: Out of 8381 patients included in ALTTO, 404 patients in the trastuzumab alone and trastuzumab plus lapatinib arms developed a DDFS event, of which 201 occurred <12 months (group A) and 203 >12 months (group B) after completion of adjuvant trastuzumab. No significant difference in location of first DDFS event was observed (p=0.073); a numerically higher number of patients in group A than in group B developed brain metastasis (26% vs 15%). Choice of first-line therapy differed between the two groups (p=0.022): in group A, more patients received lapatinib (25% vs 11%) and less pertuzumab (8% vs 17%). Median OS was 29.3 and 18.4 months in groups B and A, respectively (adjusted HR 0.69; 95% CI 0.54–0.89; p=0.004). The longer OS for patients in group B was observed across the analysed subgroups without interaction according to hormone receptor status (p=0.814) nor type of administered adjuvant anti-HER2 treatment (p=0.233). CONCLUSIONS: TFI has prognostic value in patients with HER2-positive early breast cancer treated with adjuvant trastuzumab-based therapy. TFI is a valid tool to better individualise clinical recommendations and to design future first-line treatment trials for metastatic patients.